1997
DOI: 10.1111/j.1440-1584.1997.tb00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Health Status, Treatment and Drug Use in Rural Bangladesh: A Case Study of a Village

Abstract: In Bangladesh, the government healthcare system remains a very minor source of health care for rural households. The availability of registered physicians is scare in rural areas, and the people, the majority of whom are underweight as indicated by body mass index measurement have to depend on pharmacy salespersons, quacks and herbal or spiritual healers. Unlike Australia, almost every pharmacy salesperson illegally recommends and sells prescription medicines. In addition, there are also unqualified village 'd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 1 publication
1
18
0
Order By: Relevance
“…They now often visit a doctor, if needed, but MBBS doctors are few; most are village doctors (with no formal medical education) who prescribe medicine based on their own experience and on some advertisements or booklets from pharmaceutical companies. They place greater emphasis on immediate cures and rely mostly on antibiotics and vitamins (Roy, 1997). In most cases, because there is no separate fee for a visit; these doctors charge higher prices for medicines to supplement their lower fees.…”
Section: Resultsmentioning
confidence: 99%
“…They now often visit a doctor, if needed, but MBBS doctors are few; most are village doctors (with no formal medical education) who prescribe medicine based on their own experience and on some advertisements or booklets from pharmaceutical companies. They place greater emphasis on immediate cures and rely mostly on antibiotics and vitamins (Roy, 1997). In most cases, because there is no separate fee for a visit; these doctors charge higher prices for medicines to supplement their lower fees.…”
Section: Resultsmentioning
confidence: 99%
“…12 The common patient factors involved lack of knowledge between bacterial and viral infections, expectation, satisfaction and compliance with an antibiotic prescription, notions of antibiotics effectiveness, mutual recognition, patient's pressure, the possibility of losing patients are directly associated with prescribers antibiotic prescribing behavior. 10,13,22 Consumer's ignorance, self-medication behavior, and OTC antibiotics selling aggravate misuse -100, 000 doses of antibiotics had been dispensed without a prescription in one month at Rajbari district of Bangladesh. 22 Besides, patient volume and limited time of prescribers both in public and private hospital settings are another major problem area.…”
Section: Primary Analysismentioning
confidence: 99%
“…10,13,22 Consumer's ignorance, self-medication behavior, and OTC antibiotics selling aggravate misuse -100, 000 doses of antibiotics had been dispensed without a prescription in one month at Rajbari district of Bangladesh. 22 Besides, patient volume and limited time of prescribers both in public and private hospital settings are another major problem area. Average consultation time per patient in the primary care of Bangladesh is only 54 seconds.…”
Section: Primary Analysismentioning
confidence: 99%
“…A survey in Rajbari district found that 1,00,000 antibiotic doses had been dispensed in a month without any prescription. 5 Another study depicts that on an average, 92% of medications dispensed from the pharmacies were without any prescription. 6 Currently most of the drugs in Bangladesh are prescribed or sold by non-qualified or relatively less qualified health workers.…”
Section: Introductionmentioning
confidence: 99%